2018
DOI: 10.1038/s41598-018-26894-4
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 inhibition in cells with CXCR4 mutant genome created by CRISPR-Cas9 and piggyBac recombinant technologies

Abstract: The C-X-C chemokine receptor type 4 (CXCR4) is one of the major co-receptors for human immunodeficiency virus type 1 (HIV-1) entry and is considered an important therapeutic target. However, its function in maintaining the development of hematopoietic stem cells (HSC) makes it difficult to be used for HIV-1 gene therapy with HSC transplantation. A previous report showed that the natural CXCR4 P191A mutant inhibits HIV-1 infection without any defect in HSC differentiation, which could provide a basis for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 43 publications
0
35
0
1
Order By: Relevance
“…It is used in non-viral vectors for transgenesis 17 , 18 , gene therapy 7 , 19 , insertional mutagenesis 20 , and genetic screens 21 23 . It has also found application in novel therapeutic strategies including CAR T-cell engineering 24 26 , CRISPR/Cas-mediated gene therapy 27 29 , and human induced pluripotent stem cells (iPSC) engineering 30 32 . Useful variants have been developed through random mutation including a hyperactive pB transposase called hyPBase 33 as well as one that can excise pB but cannot integrate it 34 .…”
Section: Introductionmentioning
confidence: 99%
“…It is used in non-viral vectors for transgenesis 17 , 18 , gene therapy 7 , 19 , insertional mutagenesis 20 , and genetic screens 21 23 . It has also found application in novel therapeutic strategies including CAR T-cell engineering 24 26 , CRISPR/Cas-mediated gene therapy 27 29 , and human induced pluripotent stem cells (iPSC) engineering 30 32 . Useful variants have been developed through random mutation including a hyperactive pB transposase called hyPBase 33 as well as one that can excise pB but cannot integrate it 34 .…”
Section: Introductionmentioning
confidence: 99%
“…As CXCR4 and its ligand CXC12 (SDF-1) play pivotal roles in hematopoietic/progenitor cells development and thymic differentiation (Nagasawa et al, 1996; Dar et al, 2006), we should consider the safety and side effects of clinical application by targeting CXCR4 in HSPCs. However, CXCR4-deficient human T cells remain functional in a mouse model (Chung et al, 2010; Yuan et al, 2012), and we also used CRISPR-Cas9 and piggyBac recombinant technologies to create CXCR4 P191A mutant with HIV-1 infection inhibition function and without deficiency of CXCR4 function(Liu S. et al, 2018), it is possible for CRISPR-Cas9 editing of CXCR4 in human mature post-thymic CD4+ T cells for the purpose of HIV-1/AIDS therapy.…”
Section: Crispr/cas9 Technology Application In Hiv-1/aids Treatmentmentioning
confidence: 99%
“…Modified cells showed resistance to CCR5-utilizing virus and a selective advantage over wild-type cells (Wang et al, 2014). Several studies have also reported successful inhibition of CXCR4 expression and a resultant increase in HIV-1 resistance in vitro (Hou et al, 2015; Liu et al, 2017, 2018; Wang et al, 2017). Recently, a study reported the successful ablation of both the CCR5 and CXCR4 co-receptors in vitro .…”
Section: Crispr Targeting Ccr5mentioning
confidence: 99%